Hands across Care: Art and social practice in health and elder care contexts. (June 2021) - Macarow, K.; Hilton, R.; Coombs, G.
Abstract: Objectives: The convergence of socially engaged art and innovative health care was a key focus of Space and Place in End-of-Life Care, a Swedish transdisciplinary research project (2017–2020). For this project, researchers created, facilitated, and documented a range of socially engaged art and innovative healthcare practices during their exploration of the end of life in the context of Stockholm elder care residential settings. Study design: Formulated as a year-long transdisciplinary research residency, two or more art, design, and/or innovative healthcare researchers met in a Stockholm residential elder care home on a weekly basis to observe and encounter people and place and interact, converse, produce, and exchange knowledge in collaboration with the residents, carers, management, friends, family members, and other researchers. Methods: Researchers engaged in a weekly transdisciplinary research residency in a Stockholm elder care residence to encounter and interact with the people, space and place of the study setting, and learn from and contribute to the residential home. The scientific researchers engaged in a community-based participatory action research project that utilized interviews, photo-elicitation processes, and community round table discussions. This happened in dialogue with the artistic residency process, wherein the artists collaborated with the inhabitants, staff, and visitors of the residential elder care home to produce a series of socially engaged events, experiences, and artifacts, one of which was the participatory art event, the Handfestival that is the case study of this article. Results: The weekly artistic residency for the Space and Place in End-of-Life Care project resulted in the Handfestival, a participatory art event exploring hands, touch and conversation generated by researchers from the fields of art, design, innovative health and elder care in collaboration with residents, staff and family of a Swedish elder care residence. The Handfestival is a model on the intersection between socially engaged art practices and innovative health care approaches and demonstrates how elder care residences and public health agencies could engage in regular, creative, and relational activities for the participation of inhabitants in healthcare settings. Conclusions: Socially engaged and participatory art practices increase levels of social engagement and promote a greater sense of interconnectivity within health care settings. As such, the Handfestival participatory event reveals the potential for the convergence of art and health via social practice, modeling a way to develop, orchestrate and disseminate events, experiences, and/or artifacts as health services that public health agencies can and should deliver, but might find challenging to imagine and manifest.